Museums and the creative industries: The contribution of Translation Studies - Min-Hsiu Liao (JoSTrans: The Journal of Specialised Translation)
Creative industries are now widely recognised as an important drive for economic growth around the world. The museum industry, specifically, is regarded as a crucial cultural asset in this development. Against this background, this paper explores how translation research can help improve the practice of museum translation, which in turn can help museums meet their new expectations as a cultural and creative industry. The paper begins by discussing the concepts of museums and museum translation. It then reviews the literature on translation practices in museum settings, with a view to proposing five functions of museum translation: informative, interactive, political, social-inclusive, and exhibitive. The paper continues by discussing "inter-community disjunctions" between museums and translation professionals, and suggests that Translation Studies on museum texts can have more explicit museological implications in at least two areas: economic value and social-inclusivity in museums. It is hoped this paper will stimulate much-needed theoretical and professional attention regarding the role of translation practices in the museum industry.